DIAGNOSIS OF STUDENT ERRORS IN COMPLETING SPLTV STORY QUESTIONS VISITED FROM LEARNING INTERESTS AND GENDER USING THE NEWMAN METHOD - Pangaribuan, Lena; Amin Fauzi; Pardomuan Sitompul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Student errors in solving problems often occur in the learning process, especially in the process of solving contextually integrated story problems on SPLTV material. Therefore, it is necessary to research the diagnosis of student errors in solving SPLTV story problems in terms of learning interest and gender using the Newman method. The focus of the problems studied are: 1) How are the problem solving errors of male students who have high, medium, and low learning interests in solving SPLTV story problems using the Newman method? 2) What are the problem solving errors of female students who have high, medium, and low learning interests in solving SPLTV story problems using the Newman method? This research aims to diagnose the errors of male and female students who have high, medium, and low learning interests in solving SPLTV story problems using the Newman method. This type of research is descriptive with a qualitative approach. The research subjects were 30 students of class X IPA 1 using a purposive sampling technique. Data collection was done through a learning interest questionnaire, a written test on SPLTV material, interviews based on the Newman method, and documentation. Data analysis used the Miles, Huberman, and Saldana data analysis model. Based on the research results, it can be concluded that: 1) Male students who have high learning interest make skill errors and final answer writing errors, while male students who have low learning interest make transformation errors, skill errors, and final answer writing errors. 2) Female students with high learning interest made skill errors and final answer writing errors, while female students with low learning interest made comprehension errors, transformation errors, skill errors, and final answer writing errors. Keywords: Student error, learning interest, gender, Newman method